Bubble-induced convection stabilizes the local pH during solar water splitting in neutral pH electrolytes. Issue 15 (5th July 2021) - Obata, Keisuke; Abdi, Fatwa F.
Abstract : Multiphase multiphysics simulation demonstrates the presence of bubble-induced convection in regions close to the (photo)electrode surface, which suppresses the pH gradient and the resulting concentration overpotential. Abstract : Using neutral pH buffer solutions as electrolytes offers a safe and sustainable operational condition for photoelectrochemical water splitting. However, a major challenge lies in minimizing the voltage loss due to the presence of a local pH gradient during the proton coupled electron transfer reactions. In this study, Euler–Euler multiphase fluid dynamics simulations are introduced to investigate the interplay between convection driven by the (photo)electrochemical reactions and the resulting pH gradient. Bubble-induced convection is found to dominate fluid dynamics in regions close to the electrodes and significantly suppress the local pH gradient. The influence of bubble parameters and orientation of solar water splitting devices on the local velocity and the concentration overpotential is further discussed. Finally, the positive aspects from product gas bubbles are quantitatively compared with the competing negative effects, such as surface coverage by gas bubbles and ohmic loss. These negative effects have to be minimized to fully capitalize on the beneficial contribution from bubble-induced convection.